Application of Self-Polishing Copolymer and Tin-Free Nanotechnology Paint for Ships - Yushi Wang; Cheunghwa Hsu; Guanhong Pan; Chenghao Chen (Journal of Marine Science and Engineering, 2024)
During a ship’s voyage, it is difficult to maintain its hull, and prolonged exposure to seawater can lead to the attachment of marine organisms, which can negatively impact the ship’s speed. The original self-polishing copolymer was a tributyltin-containing paint used for applying two layers of protective coating onto a ship’s bottom plate. According to International Maritime Organization (abbreviated as IMO) regulations, users are no longer allowed to use paints containing tributyltin. Therefore, manufacturers have developed a tributyltin-free paint, known as tin-free nanotechnology paint, which can be used as a replacement for the base coat on ship bottom plates. This study involves the use of a self-polishing copolymer spray and tin-free nanotechnology paint. A model coated with these two types of paint will be observed underwater to study the growth of marine organisms. Additionally, fuel consumption will be analyzed through underwater inspections and sea trials. Based on the experimental data, it is known that tin-free nanotechnology paint can significantly reduce the need for repairs in factories and greatly decrease maintenance costs when compared to self-polishing copolymers.